THE COLLOCATIONS IN THE SONG LYRICS BY ADELE AND ED SHEERAN - Serikova, A.K. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
The majority of modern song lyrics are written in accordance with the requirements of a speech culture. Moreover, we must admit that very often there are collocations in the lyrics. In this paper, we examine the theoretical issues of Collocations in Modern English and analysis of use of Collocations in the song lyrics by Adele and Ed Sheeran. This paper describes general information about nature, structure and semantic issues of Collocations and analysis about using of Collocations in the song lyrics by Adele and Ed Sheeran and its functions. The paper draws the analysis result shows that (1) Nowadays, there are a lot of songs with different kinds of collocations; (2) the song lyrics by famous singers such as Adele and Ed Sheeran consist a lot of collocations, which has different meanings.
Keywords: collocation; nature and structure of collocations; functions; song lyrics